Implementation of Business Intelligence for Sales Analysis and Customer Segmentation at XYZ Store - Azharani, Gerin; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
XYZ Retail Store has a large amount of transaction data, but it has not been optimally utilized for strategic decision making. The research aims to implement a Business Intelligence. Business Intelligence helps analyze sales data and segment key business entities, namely customers, suppliers, and products. The research methodology includes designing a datawarehouse using Kimball’s Nine Step method with MySql as the database platform. Extract, Transform, Load (ETL) process is performed to prepare the data before processing with Online Analytical Processing (OLAP) approach for multidimensional sales analysis, and Data Mining with K-Means clustering algorithm to perform segmentation. The results obtained from the entire analysis, visualized using the tools of tableau.